2023
DOI: 10.1073/pnas.2214262120
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic responses of SO 2 pollution to China’s environmental inspections

Abstract: We evaluate the effect of rotating inspections carried out by China’s central government in 2016 to 2017 in response to the country’s air pollution crisis on the environmental performance of targeted cities and coal power plants. Using a staggered difference-in-differences (DID) design, we find that during one-month inspections concentrations of sulfur dioxide (SO 2 ) at coal power plants in targeted cities are on average lower by 25 to 52% compared to not-yet-inspected cities but rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…We identify a total of 5830 coal-fired EGUs in 72 countries from the Global Coal Plant Tracker, with substitution for US EGUs using the CAMPD. We then apply the reported application rates of FGD from previous studies [2,10,[17][18][19][20], only for China (92.9%), India (5%), Japan (98%), the US (86%), and Germany (100%). For most countries where no EGU-level control information reports, we assign a percentage FGD application rate (both a high and low estimate) to each country based on the capacity and economic development (see supplementary table S4.1 for details), supplemented by a grided SO 2 emission map with a global coal-fired EGUs map [53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identify a total of 5830 coal-fired EGUs in 72 countries from the Global Coal Plant Tracker, with substitution for US EGUs using the CAMPD. We then apply the reported application rates of FGD from previous studies [2,10,[17][18][19][20], only for China (92.9%), India (5%), Japan (98%), the US (86%), and Germany (100%). For most countries where no EGU-level control information reports, we assign a percentage FGD application rate (both a high and low estimate) to each country based on the capacity and economic development (see supplementary table S4.1 for details), supplemented by a grided SO 2 emission map with a global coal-fired EGUs map [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining coal EGUs, where FGD is not feasible or not cost-effective to install, are likely to be phased out due to tightening emission regulations and increasing operation costs [16]. In China, over 92.9% of coal plants have been equipped with FGD as of 2020 [17,18]. In Japan, 98% of the coal plants have installed FGD as of 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In China, with the world's largest fleet of SO 2 scrubbers, between 2006 and 2009, the share of the coal power capacity with scrubbers increased from 10% to 71% [33]. By 2017 in China, one study found that ∼80% of the plants in their sample had SO 2 scrubbers installed [34]. However, this study found that the effectiveness of SO 2 removal (scrubber efficiency) varies at coal power plants at the low end from 25%-54% versus 52%-62% at the high end, depending on government oversight [34].…”
Section: Sulfur Scrubber Efficiencymentioning
confidence: 99%
“…By 2017 in China, one study found that ∼80% of the plants in their sample had SO 2 scrubbers installed [34]. However, this study found that the effectiveness of SO 2 removal (scrubber efficiency) varies at coal power plants at the low end from 25%-54% versus 52%-62% at the high end, depending on government oversight [34]. In the US, scrubber efficiency is reported between 85% to 95%, with newer designs capable of achieving 98% [32].…”
Section: Sulfur Scrubber Efficiencymentioning
confidence: 99%